2019
DOI: 10.1002/ejsp.2624
|View full text |Cite
|
Sign up to set email alerts
|

Toleration and prejudice‐reduction: Two ways of improving intergroup relations

Abstract: While a large body of social psychological research has shed light on the nature of prejudice and how to reduce it, we argue that such work does not address situations of cultural or religious outgroup beliefs and practices that are considered incompatible with one's own. The present theoretical article contrasts a prejudice‐reduction approach with a toleration‐based approach to consider the differences each have with regard to the attitude object they focus upon, the perceived reasonableness of the attitude, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
54
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 158 publications
5
54
2
2
Order By: Relevance
“…In principle, online manipulations of control could be weaker than those in the laboratory, accounting for the lack of support for the control hypothesis. As an empirical matter, however, there is no evidence that effects in this paradigm depend on sample type [68]. In a recent meta-analysis of experimental manipulations of control on conspiracy beliefs [68] conducted on 45 effect sizes across 23 studies (including those reported here), we found no moderating effect of sample type (MTurk vs. students vs. other).…”
Section: Plos Onecontrasting
confidence: 52%
See 1 more Smart Citation
“…In principle, online manipulations of control could be weaker than those in the laboratory, accounting for the lack of support for the control hypothesis. As an empirical matter, however, there is no evidence that effects in this paradigm depend on sample type [68]. In a recent meta-analysis of experimental manipulations of control on conspiracy beliefs [68] conducted on 45 effect sizes across 23 studies (including those reported here), we found no moderating effect of sample type (MTurk vs. students vs. other).…”
Section: Plos Onecontrasting
confidence: 52%
“…As an empirical matter, however, there is no evidence that effects in this paradigm depend on sample type [68]. In a recent meta-analysis of experimental manipulations of control on conspiracy beliefs [68] conducted on 45 effect sizes across 23 studies (including those reported here), we found no moderating effect of sample type (MTurk vs. students vs. other). Thus, although it is important to continue to examine the role of control threats in diverse samples and contexts, the current data, despite being collected online, nevertheless challenge the hypothesis that such threats account for conspiracy beliefs in any significant way.…”
Section: Plos Onecontrasting
confidence: 52%
“…Because toleration is widely promoted across a wide range of settings and across the political spectrum for establishing multicultural justice and peaceful coexistence, it is important to systematically investigate the different complexities and paradoxes involved in toleration. Although prior work provided a theoretical account of the social psychological processes involved in toleration (Verkuyten & Yogeeswaran, 2017; Verkuyten, Yogeeswaran, & Adelman, 2020), in this article, we delve deeply into what it means to be tolerated and the possible implications for minority and disadvantaged target individuals. We tried to offer a mapping of a terrain that is largely unexplored by psychologists by identifying important questions and theoretical avenues to explore and develop.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, addressing deliberative intolerance requires a weighing of the reasons for not allowing dissenting practices and beliefs (e.g., harm and rights principle) that might trump those for accepting these (e.g., religious freedom). Here, making people aware of and inducing them to carefully think about the nature and relative importance of the reasons for why and when something cannot be tolerated is central (Verkuyten, Yogeeswaran, & Adelman, 2020). This sort of reflective reasoning decreases one's reliance on intuition and therefore can lead to a more reflective than intuitive judgment about not tolerating something.…”
Section: Resultsmentioning
confidence: 99%